Valoración del estado nutricional de los niños y niñas del Tercero y Cuarto Año de Educación Básica de la Escuela José Miguel Burneo (Obrapía) de la ciudad de Loja. - Oviedo Sarango, Katty Karina (2016)
Nutritional status is the condition of the organism that results from the relationship between individual’s nutritional needs, ingestion, absorption and biological utilization of nutrients contained in food. The objectives are to find out the children’s nutritional status of the school José Miguel Burneo (Obrapía) in the city of Loja, and to relate the nutritional status of the children with their socioeconomic status. The study was of type a descriptive section in which all the children participated in the third and fourth year of basic education. This made up of 100 students. A survey was applied to the parents, and anthropometric measures (weight / height) were taken to all the boys and girls being studied. The most relevant results were: 19% of children were overweight / obese and 13% had mild / moderate malnutrition, 67% of the low socioeconomic status belonged to the lowest level and 10% to the marginal level. It was concluded that the nutritional status of each individual does not depend directly on the socioeconomic status as such; however, it is influenced by other factors. Key words: Nutritional status, Body mass index, anthropometry, boys and girls.